Most Preschoolers Don't Know Most. Issue 4 (2nd October 2018) - Sullivan, Jessica; Bale, Alan; Barner, David
ABSTRACT: Recently, researchers interested in the nature and origins of semantic representations have investigated an especially informative case study: The acquisition of the word most —a quantifier which by all accounts demands a sophisticated second-order logic, and which therefore poses an interesting challenge to theories of language acquisition. According to some reports, children acquire most as early as three years of age, suggesting that it does not draw on cardinal representations of quantity (contrary to some formal accounts), since adult-like knowledge of counting emerges later in development. Other studies, however, have provided evidence that children acquire most much later—possibly by the age of 6 or 7—thereby drawing this logic into question. Here we explore this issue by conducting a series of experiments that probed children's knowledge of most in different ways. We conclude that children do not acquire an adult-like meaning for most until very late in development—around the age of 6—and that certain behaviors which appear consistent with earlier knowledge are better explained by children's well-attested bias to select larger sets (a "more" bias), especially when tested with unfamiliar words.